Characteristics of Learning Arabic Using the Totally Physical Response Method at Palembang Elementary School - Nurani, Qoim (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2022)
The purpose of this research is to define the characteristics of learning Arabic using the totally physical response method at SD Muhammadiyah 6 Palembang, to find out about the implementation of the totally physical response method in learning Arabic at SD Muhammadiyah 6 Palembang and to find out the advantages and disadvantages of the totally physical response method in language learning. Arab. In this study used a qualitative approach with a type of descriptive method. Researchers used descriptive methods and data collection methods in interviews, observation, and documentation. The results of this study are the process of implementing Arabic learning using the method Totally Physical Respons in SD Muhammadiyah 6 Palembang, namely the teacher acts as a model or example, the teacher can give instructions to students and then exemplify or practice in front of students so that students can understand the instructions given and can follow them. The advantage is that it can make students in the learning process more enjoyable, students are free from stress, and learning is more meaningful by demonstrating that students more easily understand and understand in learning Arabic. The drawback is that some students do not want to demonstrate because they are shy.